Hermaphroditism in Marijuana (Cannabis sativa L.) Inflorescences – Impact on Floral Morphology, Seed Formation, Progeny Sex Ratios, and Genetic Variation - Punja, Zamir K.; Holmes, Janesse E. (Frontiers in Plant Science, 2020)
Cannabis sativa L. (hemp, marijuana) produces male and female inflorescences on different plants (dioecious). In commercial production, marijuana plants are all genetically female and male plants are undesired. On occasion, spontaneously occurring hermaphroditic inflorescences, which are pistillate flowers accompanied by spontaneous production of anthers, can lead to undesired seed formation. We studied hermaphroditism in marijuana strains with the objective of describing the morphological features of this unique phenotype. We also hypothesized that hermaphroditism would impact progeny sex ratios and affect genetic diversity. Anthers were collected from hermaphroditic inflorescences that were observed in three commercial female strains (genotypes). The morphological features, pollen production and germination were compared to staminate inflorescences on male plants using light and scanning electron microscopy. Seeds from hermaphroditic plants were harvested, germinated and seedlings were tested for gender using a PCR-based assay. The genetic variation among seedlings derived from hermaphroditic seeds was also compared to that derived from cross-fertilized seeds using six ISSR primers. Nei’s index of gene diversity and Shannon’s Information index were calculated for hermaphroditic and cross-fertilized populations. The morphology of anthers in hermaphroditic inflorescences was found to be similar to that in staminate flowers. In PCR assays, female and male seedlings both produced a 540 bp size fragment, while a 390 bp band was present only in male plants. Seedlings from hermaphroditic seeds, as well as anther tissues, were all observed to have the female banding pattern. In comparison, seedlings derived from cross-fertilized seeds yielded a male:female expression ratio of approximately 1:1 in two different strains of marijuana. The percentage of polymorphic loci ranged from 44% to 72% in hermaphroditic and cross-fertilized populations. Nei’s index of gene diversity and Shannon’s Information index were similar for both populations. Uniquely, hermaphroditic inflorescences produce seeds which give rise only to genetically female plants. The extent of genetic variation after one generation of selfing was similar to that among progeny from cross-fertilized seeds. The presence of Copia-like retrotransposons within the C. sativa genome was established through sequence comparisons of the 540 bp fragment. Their functions or association with the expression of male or female phenotype requires further study.